Effect of Statin Therapy on Incident Type 2 Diabetes Mellitus in Patients With Clinically Manifest Vascular Disease - Van De Woestijne, Anton P.; Van Der Graaf, Yolanda; Westerink, Jan; Nathoe, Hendrik M.; Visseren, Frank L J (Elsevier, 2015)
Several trials and cohort studies have shown an increased incidence of type 2 diabetes mellitus (T2DM) in patients using statins. Whether this only applies to patients at already high risk for the development of T2DM or for all patients is still a matter of debate. In the present prospective cohort study of 4,645 patients with established vascular disease without DM at baseline, 3,057 patients used statins at baseline, of whom 1,608 used intensive statin therapy, defined as statin therapy theoretically lowering low-density lipoprotein cholesterol with ≥40%. Cox proportional hazards models were used to estimate the risk of incident T2DM with (intensive) statin therapy. Statin therapy was associated with increased risk of incident T2DM (hazard ratio 1.63; 95% confidence interval 1.15 to 2.32) when adjusted for age, gender, body mass index, plasma high-density lipoprotein cholesterol, and plasma triglyceride levels. Intensive statin therapy tended to be related to a higher risk of T2DM compared with moderate statin therapy (hazard ratio 1.22; 95% confidence interval 0.92 to 1.61, adjusted for age, gender, body mass index, plasma high-density lipoprotein cholesterol, and plasma triglyceride levels). The increase in risk was regardless of the number of metabolic syndrome characteristics or insulin resistance but was particularly present in patients with low baseline glucose levels (<5.6 mmol/L; p for interaction 2.9 × 10-7). In conclusion, statin use increases the risk of incident T2DM in patients with clinically manifest vascular disease. The increase in risk was independent of the number of metabolic syndrome criteria and was even more pronounced in patients with low baseline glucose levels.
Keywords: INSULIN-RESISTANCE; RANDOMIZED-TRIALS; LDL CHOLESTEROL; RISK; METAANALYSIS; POPULATION; EFFICACY; GLUCOSE; SAFETY; Taverne; Journal Article; Research Support, Non-U.S. Gov't